The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cpdd.896
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐ and Positive‐Controlled, Three‐Way Crossover Study in Healthy Participants to Investigate the Effect of Savolitinib on the QTc Interval

Abstract: Savolitinib (AZD6094, HMPL-504, volitinib) is an oral, bioavailable, selective MET-tyrosine kinase inhibitor. This randomized, double-blind, 3-way, crossover phase 1 study of savolitinib versus moxifloxacin (positive control) and placeboevaluated effects on the QT interval after a single savolitinib dose. Healthy non-Japanese men were randomized to 1 of 6 treatment sequences, receiving single doses of savolitinib 600 mg, moxifloxacin 400 mg, and placebo. The primary end point was time-matched, placebo-adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
3
8
0
Order By: Relevance
“…When midazolam was dosed in combination with savolitinib compared with midazolam alone, PK parameters ( C max , AUC and AUC [0‐ t ] ) were similar, with all 90% CIs encompassing unity. The PK exposure of savolitinib (in combination with midazolam) in the midazolam study (Table 2) was similar to the exposure of savolitinib observed in the famotidine or rifampicin studies when dosed alone; furthermore, the ranges in exposure appear to overlap compared to previous studies, even though the mean exposure is slightly lower 6,8 . Moreover, the metabolite‐to‐parent ratios for both M2 and M3 were similar across these studies, indicating that their contribution to the interaction has also been evaluated; this suggests that the exposure of savolitinib and its metabolites, M2 and M3, was sufficient to evaluate the effect on midazolam in this study.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…When midazolam was dosed in combination with savolitinib compared with midazolam alone, PK parameters ( C max , AUC and AUC [0‐ t ] ) were similar, with all 90% CIs encompassing unity. The PK exposure of savolitinib (in combination with midazolam) in the midazolam study (Table 2) was similar to the exposure of savolitinib observed in the famotidine or rifampicin studies when dosed alone; furthermore, the ranges in exposure appear to overlap compared to previous studies, even though the mean exposure is slightly lower 6,8 . Moreover, the metabolite‐to‐parent ratios for both M2 and M3 were similar across these studies, indicating that their contribution to the interaction has also been evaluated; this suggests that the exposure of savolitinib and its metabolites, M2 and M3, was sufficient to evaluate the effect on midazolam in this study.…”
Section: Discussionsupporting
confidence: 67%
“…The PK exposure of savolitinib (in combination with midazolam) in the midazolam study (Table 2 ) was similar to the exposure of savolitinib observed in the famotidine or rifampicin studies when dosed alone; furthermore, the ranges in exposure appear to overlap compared to previous studies, even though the mean exposure is slightly lower. 6 , 8 Moreover, the metabolite‐to‐parent ratios for both M2 and M3 were similar across these studies, indicating that their contribution to the interaction has also been evaluated; this suggests that the exposure of savolitinib and its metabolites, M2 and M3, was sufficient to evaluate the effect on midazolam in this study. Our results indicate that co‐administration of midazolam with savolitinib has no effect on midazolam PK and thereby, on the CYP3A4 pathway.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations